Originally Posted by

**Paze** Hi Uperkurk.

Your method is correct.

Your answer also seems to be correct. You are left with $\displaystyle a=0$ So by plugging that into either one of your equations (I'm choosing the first one for my example), you get $\displaystyle 4\cdot 0-6b\right)=15$ It seems that by solving this equation you get $\displaystyle b=\frac{-5}{2}$ which is harmonious with the answer.

For a more in-depth view on how to solve the equation

$\displaystyle \\4\cdot 0-6b=15\\\\0-6b=15\\\\-6b=15\\\\b=\frac{15}{-6}\\\\b=-\frac{5}{2}$

Does this clear it up for you?